Honour bound eaudiobook - Harper, Helen (Highland Magic, 2016)
Integrity Taylor should have been a Clan princess. Instead she's lived a life on the very periphery of society. However, now that she's learned more about her heritage and the magic that she's capable of wielding, she's not going to hide in the shadows any longer. The once-in-a-generation Sidhe Games are going to provide the perfect opportunity for her to win back her birthright, and the fact that she'll be going head-to-head, toe-to-toe, and mouth-to-mouth with golden haired Byron Moncrieffe might just be the icing on the cake.